Peak expiratory flow rate among workers engaged in stone crushing units surrounding, Gulbarga city - Deshmukh, Sunil A.; Nigudgi, S. R.; Reddy, Srinivas (International Journal Of Community Medicine And Public Health, 2017)
Background: A periodic measurement of lung functions would be a guiding principle to detect the lung abnormalities in the early stages and among lung function tests, peak expiratory flow rate (PEFR) is useful. The industrial workers are subjected to illness suffered not only of those of fellow citizens but are also subjected to certain illness due to mainly their work environment which is peculiar to each work place or industry. The objective of the study was aimed at the PEFR of workers in stone crushing units, Gulbarga city. The authors were also aimed at the study of the factors influencing PEFR of the workers and to suggest the various measures for the improvement in the health status of the workers. Methods: The study was undertaken among the workers engaged in stone crushing units and related respiratory ailment among workers based on PEFR in stone crushing units surrounding Gulbarga city, Karnataka, India. The study sample comprised a total of 150 workers examined. Results: The result of the study showed that 51 (34%) workers with less than 400 L/min PEFR having signs and symptoms like breathlessness and cough were as 99 (66%) workers with PEFR 400-600 L/min were normal. The study also shows that there is highly significant association between lung function parameter (PEFR) with duration of exposure. Conclusions: The result indicated the need to increase awareness among the workers regarding the dust generated by crushing units.